LINEAR PROGRAMMING AS A DECISION-MAKING TOOL IN MAXIMIZED PROFITS OF MACRAME MICRO-CRAFT BUSINESSES - Dian Yulis Wulandari (Yayasan Sinergi Multidimensi Kreatif, 2025)
Macrame craft microbusiness is one of the creative economic sectors that has high potential in increasing community income. However, limited production resources such as the number of threads, working time, and availability of accessories often cause business actors to experience difficulties in determining the right production composition to obtain maximum profits. This study aims to analyze and formulate a Linear Programming model as a decision-making tool in maximizing the profits of macrame craft microbusinesses. The research method used is a quantitative approach by identifying decision variables, objective functions, and production constraints based on data on raw material capacity, processing duration, and profits for each type of product. The mathematical model solution is carried out using the Simplex method to obtain the optimal combination of product quantities. The results show that Type 1: Macrame Keychain is produced in a total of 40 Units, Type 2: Macrame Small Wall Hanging is produced in a total of 30 Units and Type 3: Macrame Plant Hanger is not produced. The goal of minimizing the total thread encourages production as much as possible from the product with the smallest (Type 1), up to the production/demand limit . After is met, take the product with the next smallest (Type 2). Since other constraints (nodes, clock, S) do not preclude this choice in this example, the greedy solution is optimal.